Antiviral Drugs Intervention Strategies - Badria, Farid A. (IntechOpen, 2022)
With the increasing emergence of viral infections worldwide, researchers are working to develop new and non-conventional treatments for infectious diseases. This is particularly true for SARS-CoV-2, which initiated a pandemic in 2019. With a focus on coronavirus, this book provides an overview of antiviral agents and new approaches to drug design. It includes five chapters that address new avenues for drug discovery, reprofiling of current drugs, computer-aided drug design, and more.